2013
DOI: 10.1016/j.schres.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mortality in schizophrenia: Defining a critical period for prevention

Abstract: Objective Better understanding of the temporal development of cardiovascular risk will permit more targeted prevention of premature cardiovascular mortality in schizophrenia. Methods The sample for this analysis was drawn from referrals (between 2006-‘11) to an early psychosis clinic based in a U.S. urban community mental health center. 76 individuals with schizophrenia who were young (mean 22.4 years, SD 4.8), early course (median duration of illness 31 weeks) and with minimal prior antipsychotic exposure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
2
44
1
1
Order By: Relevance
“…4,62 Lifestyle change incorporated in phase-specific FEP care could reap significant health and quality of life benefits several decades later for the FEP population. However, first and foremost, care in initial medication choice represents a relatively easy and inexpensive preventive health intervention for FEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,62 Lifestyle change incorporated in phase-specific FEP care could reap significant health and quality of life benefits several decades later for the FEP population. However, first and foremost, care in initial medication choice represents a relatively easy and inexpensive preventive health intervention for FEP.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that cardiovascular risk doubles in the first year of psychotic illness. 4 This presents a rare opportunity for a 'critical period' of intervention to prevent morbidity and mortality and improve quality of life for psychosis early intervention programmes several decades later.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, clinicians have speculated about the potential options to exert therapeutic interventions during the early stages of SZ, with the goal of delaying or averting the illness and/or its complications (Sullivan, 1994; Srihari et al, 2013). However, effective early interventions require the ability to correctly identify the patients that will have a poor clinical course and more comorbid conditions, like MS.…”
Section: Schizophrenia and Sphingolipidsmentioning
confidence: 99%
“…Patients and healthy controls showed comparable adaptations to endurance training, as assessed by physical working capacity cardiovascular health, for example, in people without a psychiatric disorder [3]. Patients with schizophrenia are on average less active, less fit and at higher risk of cardiovascular and metabolic diseases than people without psychiatric disorders [4,5] and consequently show a higher excess mortality [6]. Endurance training might be beneficial for patients with schizophrenia via multiple ways.…”
Section: Introductionmentioning
confidence: 99%